Charting the path to the implementation of universal health coverage policy in Nigeria through the lens of Delphi methodology - Jibril M. Bashar; Sulaiman Hadiza; Ozoilo J. Ugochi; Lawal S. Muhammad; Adeoye Olufemi; Ukoh Eberechi; Yakubu Agada-Amade; Alhassan Yusuf; Abdulhamid H. Abdullahi; Hassan S. Musa; Ahmad A. Ibrahim; Kalu-Umeh Nnennaya; et al. (BMC Health Services Research)
Abstract Background Expanding access to equitable health insurance is an important lever towards the overall strategy for achieving universal health coverage. In Nigeria, health insurance coverage is low with a renewed government action on increasing access to and coverage of high-quality healthcare services to citizens, particularly for the vulnerable and poor population. Therefore, our study co-creates the priorities for expanding health insurance in Nigeria, focusing on key policy reforms, public advocacy, and innovative financing strategies to ensure broader and more equitable coverage for the population. Methodology We employed a Delphi approach methodology through strategic health insurance meetings with a diverse multidisciplinary panel of 125 stakeholders including representatives of accredited Health Insurance Maintenance Organizations, Heads of States Social Health Insurance Agencies, Development Partners representatives, academics, government officials, national health insurance authority expanded management team and experts in health insurance across all the states of Nigeria to recommend specific actions towards health insurance expansion and universal health coverage in Nigeria. Results The participants/panels were able to come up with a consensus on 66 priorities for health insurance expansion in Nigeria working with stakeholders within the Nigerian health insurance ecosystem across the 36 states and Nigeria’s FCT. From these priorities, seven priority areas and 17 themes were derived that should be considered by the government, policymakers, regulators, and practitioners to deepen health insurance penetration in Nigeria. These seven priority areas that have been identified include enrolment, equity, organizational health and structure, data and technology, quality, market efficiency, and citizen engagement. Conclusion The priorities identified for health insurance expansion in Nigeria will go a long way in shaping health insurance. We hope that government, policymakers, regulators, and practitioners in the health ecosystem will use these social policy actions to set priorities for increasing health insurance coverage and address inadequacies to accelerate the drive towards the attainment of UHC by 2030.